Abdominal ultrasound features and reference values in 21 healthy rabbits. (24th January 2015) - Banzato, T.; Bellini, L.; Contiero, B.; Selleri, P.; Zotti, A.
Abstract : This study aimed to determine the ultrasonographic features and reference values of the abdominal anatomy in mixed‐breed dwarf rabbits. Complete abdominal ultrasonographic examination was performed in 21 mixed‐breed rabbits (12 males and 9 females) referred for examination to the Department of Animal Medicine, Production and Health, University of Padua, Italy. All animals were sedated during the procedure. The ultrasonographic anatomy of the abdomen was determined, including measurement (mean±SD) of the right kidney (length 2.87±0.34 mm; width 1.62±0.17 mm; height 1.66±0.14 mm) and left kidney (length 2.86±0.33 mm; width 1.72±0.19; height 1.58±0.15 mm), left adrenal gland (width 0.38±0.11 mm; length 0.71±0.14), right adrenal gland (width 0.34±0.08 mm; length 0.73±0.15 mm) and thickness of the walls of the stomach (0.10±0.01 mm), pylorus (0.28±0.04 mm), duodenum (0.19±0.04 mm), sacculus rotundus (0.22±0.06 mm), caecum (0.08±0.01 mm), appendix (0.19±0.04 mm), spiral loop of the ascending colon (0.14±0.04 mm) and distal colon (0.10±0.02 mm). A significant positive correlation between bodyweight and kidney size, adrenal gland length, stomach wall and sacculus rotundus wall was detected.